DIGITALIZATION IN THE CONSTRUCTION INDUSTRY - I. Kravchenko (Вестник Северо-Кавказского федерального университета)
Construction is an industry that includes a huge number of stages in the life cycle of a project, and if you apply appropriate technologies based on numbers on each of them, you can optimize each of them by applying an information technology model, whose tools (robots) positively affect the workflow and production results in general. The subject of this study is the definition of a digitalization tool for construction using the life cycle of an object as an example. The study of the information technology model of th deve e project life cycle in small business, as a tool to improve the efficiency of the workflow in the current lopment trends of the construction sector.